Expression Profile of Fibroblast Growth Factor Receptors, Keratinocyte Differentiation Markers, and Epithelial Mesenchymal Transition-Related Genes in Actinic Keratosis: A Possible Predictive Factor for Malignant Progression? - Persechino, Flavia (Biology (Basel), 2021)
SIMPLE SUMMARY: In this work, we checked the modulation of Fibroblast Growth Factor Receptors (FGFRs) along with differentiation-related and epithelial-to-mesenchymal transition (EMT)-related markers to identify expression profiles that could be predictive for actinic keratosis (AK) progression through the “differentiated” pathway. We found that the downregulation of the analyzed differentiation markers, but not the modulation of the EMT-related markers, correlated with the canonical progression of AK. In addition, the observed modulation of FGFR2 mesenchymal/epithelial isoforms compatible with FGFR2 isoform switch, as well as the upregulation of FGFR4 suggested their correlation with early steps of AK pathogenesis. In contrast, the increase of mesenchymal FGFR3c isoform expression appeared to suggest that this event correlated with late steps of AK progression. In addition, the strong modulation of filaggrin (FIL), Snail1, as well as of FGFR2c, FGFR4, and their ligand Fibroblast Growth Factor 2 (FGF2), observed in some of the keratinocytic intraepithelial neoplasia grade I (KIN I) samples, may indicate that they could be molecular markers predictive for those KIN I lesions destined to a direct progression to squamous cell carcinoma (SCC) through the “differentiated” pathway. ABSTRACT: Actinic keratosis (AK) is the ultra violet (UV)-induced preneoplastic skin lesion clinically classified in low (KIN I), intermediate (KIN II), and high (KIN III) grade lesions. In this work we analyzed the expression of Fibroblast Growth Factor Receptors (FGFRs), as well as of keratinocyte differentiation and epithelial-to-mesenchymal transition (EMT)-related markers in differentially graded AK lesions, in order to identify specific expression profiles that could be predictive for direct progression of some KIN I lesions towards squamous cell carcinoma (SCC). Our molecular analysis showed that the keratinocyte differentiation markers keratin 1 (K1), desmoglein-1 (DSG1), and filaggrin (FIL) were progressively downregulated in KIN I, II, and III lesions, while the modulation of epithelial/mesenchymal markers and the induction of the transcription factors Snail1 and Zinc finger E-box-binding homeobox 1 (ZEB1) compatible with pathological EMT, even if observable, did not appear to correlate with AK progression. Concerning FGFRs, a modulation of epithelial isoform of FGFR2 (FGFR2b) and the mesenchymal FGFR2c isoform compatible with an FGFR2 isoform switch, as well as FGFR4 upregulation were observed starting from KIN I lesions, suggesting that they could be events involved in early steps of AK pathogenesis. In contrast, the increase of FGFR3c expression, mainly appreciable in KIN II and KIN III lesions, suggested a correlation with AK late progression. Interestingly, the strong modulation of FIL, Snail1, as well as of FGFR2c, FGFR4, and of their ligand FGF2, observed in some of the KIN I samples, may indicate that they could be molecular markers predictive for those low graded lesions destined to a direct progression to SCC. In conclusion, our data point on the identification of molecular markers predictive for AK rapid progression through the “differentiated” pathway. Our results also represent an important step that, in future, will help to clarify the molecular mechanisms underlying FGFR signaling deregulation in epithelial tissues during the switch from the pre-neoplastic to the oncogenic malignant phenotype.